Affecting an Ultra‐High Work Function of Silver. (30th January 2020) - He, Jin; Armstrong, Jeff; Cong, Peixi; Menagen, Barak; Igaher, Lior; Beale, Andrew M.; Etgar, Lioz; Avnir, David
Abstract: An ultra‐high increase in the WF of silver, from 4.26 to 7.42 eV, that is, an increase of up to circa 3.1 eV is reported. This is the highest WF increase on record for metals and is supported by recent computational studies which predict the potential ability to affect an increase of the WF of metals by more than 4 eV. We achieved the ultra‐high increase by a new approach: Rather than using the common method of 2D adsorption of polar molecules layers on the metal surface, WF modifying components, l ‐cysteine and Zn(OH)2, were incorporated within the metal, resulting in a 3D architecture. Detailed material characterization by a large array of analytical methods was carried out, the combination of which points to a WF enhancement mechanism which is based on directly affecting the charge transfer ability of the metal separately by cysteine and hydrolyzed zinc(II), and synergistically by the combination of the two through the known Zn‐cysteine finger redox trap effect. Abstract : Eine ultrahohe Steigerung der Austrittsarbeit (WF) von Silber von 4.26 auf 7.42 eV wird beim dualen Einschluss der WF‐modifizierenden Komponenten l ‐Cystein und Zn(OH)2 in das Metall beobachtet. Diese Verstärkung basiert auf der direkten Beeinflussung der Ladungstransferfähigkeit des Metalls – zum einen separat durch Cystein und hydrolysiertes Zink(II), zum anderen synergistisch durch die Kombination der beiden durch den Zn‐Cysteinfinger‐Redoxfallen‐Effekt.